Navigating Eros and Thanatos: a genre and appraisal analysis of Virginia Woolf’s suicide note and John Keats’ last letter - Sadia Irshad,; Sajid Ali,; Shah Muhammad, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study aims to analyze Freudian life and death drives, commonly referred to as Eros and Thanatos, through the lens of systemic functional linguistics, particularly focusing on the interpersonal meaning-making process. The texts selected for this analysis are Virginia Woolf's suicide note and John Keats's last letter to his friend Charles Brown. These letters are significant as they were composed shortly before the authors' deaths—Woolf by suicide and Keats due to tuberculosis—providing a poignant context for examining their expressions of life and death.The analysis is framed within the genre of letters, which allows for a nuanced understanding of the contextual factors influencing each writer's expression of Eros and Thanatos. By evaluating these texts, the study seeks to uncover shared values surrounding these drives (Freud, 1961) using appraisal theory, an extension of systemic functional linguistics (SFL) that focuses on interpersonal meaning (Martin & White, 2005). The research is specifically limited to the attitude system of appraisal, enabling an exploration of interpersonal attitudinal markers between the writers and their recipients. This text analysis employs descriptive and interpretive techniques, connecting interpretations with the three major systems of attitude: Affect, Judgment, and Appreciation. This framework will facilitate a comparison of the emotional landscapes reflected in the letters, highlighting both similarities and differences in how Woolf and Keats confront their impending deaths. The study concludes that life and death drives are instinctual forces shaped by both physical and mental health contexts. By situating these texts within their letter genre, the analysis provides a richer understanding of how Eros and Thanatos manifest in personal correspondence at critical moments in life.